Effects of PEF-Assisted Freeze-Drying on Protein Quality, Microstructure, and Digestibility in Chilean Abalone “Loco” (Concholepas concholepas) Mollusk - Palma-Acevedo, Anais; Pérez-Won, Mario; Tabilo-Munizaga, Gipsy; Ortiz-Viedma, Jaime; Lemus-Mondaca, Roberto (Frontiers in Nutrition, 2022)
The purpose of this study was to apply different pulsed electric fields (PEF) conditions as a pretreatment to the freeze-drying (FD) process of Chilean abalone and assessment the effects on protein quality, microstructure, and digestibility in the freeze-dried product. The treatments were applied PEF (0.5, 1.0, and 2.0 kV cm-1) and cooking (CO) at 100 °C ×15 min. Then the performances were subjected to a freeze-drying process. The PEF+CO pretreated freeze-dried samples showed shorter process times than the freeze-dried control sample without PEF+CO, where the treatment PEF at 2.0 kV cm-1 reached the shortest time. In addition, the above samples presented the best textural parameters, but a low protein content. The thermal properties indicate a total denaturation of the proteins, where the amide I region presented greater mobility in the sample pretreated with an electric field of 2.0 kV cm-1. The assay for digestibility shows better hydrolysis for the 2.0 kV cm-1 PEF sample and a higher C-PER (Computer - Protein Efficiency Ratio). Thereby, variations in thermal behavior and physicochemical parameters compared to combined PEF+CO pretreatments were observed; in addition, the high protein quality and digestibility of pretreated freeze-dried Chilean abalones were maintained to the desired properties (texture, and C-PER) and conditions (freeze-drying time).